Epithelial-mesenchymal transition as a potential biomarker for identifying responders to immune checkpoint inhibitor therapy in lung adenocarcinoma - Lowe, Devin B.; La-Beck, Ninh M. (Translational Cancer Research; Vol 5, No 2 (April 22, 2016): Translational Cancer Research, 2016)
It is increasingly evident that the immune system plays critical roles in both cancer progression and regression, and it has been a target for anticancer therapies for over a hundred years (1). Until recently, however, attempts at stimulating a de novo immune response against tumor cells have met with limited clinical success largely due to immunoinhibitory pathways that downregulate the host immune response against cancer. The discovery of immune checkpoints revealed one of these key immunoinhibitory mechanisms and has led to the development of therapeutic inhibitors that essentially release the brakes on the immune system. The last 5 years has seen a revolution in the treatment of melanoma and non-small cell lung cancer with the regulatory approval of three immune checkpoint inhibitors, ipilimumab which targets the cytotoxic lymphocyte—associated protein 4 (CTLA-4) pathway, and nivolumab and pembrolizumab which target the programmed cell death protein 1 (PD-1) pathway. Several clinical trials have shown that these immune checkpoint inhibitors can induce a durable long-term response and prolong overall survival (2). In addition, they appear to be more tolerable than traditional cytotoxic chemotherapy. However, these benefits are not without major drawbacks as only 20–26% of patients respond to CTLA-4 targeted therapy and fewer than 40% respond to PD-1 targeted agents (2). Moreover, up to 15% of patients can experience severe dose limiting immune related adverse events (2). Thus, there is a critical need to develop strategies to identify patients who are likely to respond to immune checkpoint inhibitor therapy.